Ex vivo, microelectrode analysis of conduction through the AV node of wild‐type and Nkx2‐5 mutant mouse hearts as guided by a Cx40‐eGFP transgenic reporter. Issue 4 (23rd April 2014) - Gazit, Avihu Z.; Li, Alex; Choi, Jacob S.; Miquerol, Lucile; Jay, Patrick Y.
Abstract Mutations of the cardiac transcription factor NKX2‐5 cause hypoplastic development of the AV node and conduction block. How the anatomy of the mutant AV node relates to its function is unknown. We thus studied conduction through the AV nodal region in ex vivo preparations of wild‐type and Nkx2‐5+/− mouse hearts in which the central conduction system was highlighted by a transgenic Cx40‐eGFP reporter. Fluorescence imaging guided electrode placement and pacing of the inferior and superior approaches to the AV node. Nkx2‐5+/− hearts had a prolonged atrio‐His interval compared to the wild type, consistent with previous in vivo observations. The conduction time to the His bundle from the Cx40− AV nodal region that is superior to and immediately adjacent to the Cx40+ lower node is slightly, but not significantly greater in Nkx2‐5+/− than wild‐type hearts. A novel phenotype was also observed. Pacing the Cx40− inferior approach to the AV node with increasing stimulus strength led to progressive shortening of the stimulus‐to‐His conduction interval in wild‐type but not Nkx2‐5+/− hearts. The strength of pacing at the Cx40− superior approach had no effect on the conduction interval in either group. The prolonged AV delay in the Nkx2‐5+/− heart appears to arise before the Cx40+ lower node. Whether the pacing phenotype explains the mutant's conduction defect is uncertain, but the observation adds to a number of unique properties of the inferior approach to the AV node.